How SD-OCT is changing our view of DME - Salam, Adzura; Framme, Carsten; Wolf, Sebastian (Wolters Kluwer Pharma Solutions, Inc., 2010)
In diabetic macular edema, vascular endothelial damage is a major event that results in the breakdown of the inner blood-retinal barrier and accumulation of fluid and serum macromolecules in the intracellular space.1 The Wisconsin Epidemiologic Study of Diabetic Retinopathy reported that 32% of patients developed macular edema within 22 to 24 years of diabetes diagnosis.2